2008
DOI: 10.1177/0741932507309717
|View full text |Cite
|
Sign up to set email alerts
|

Creating a Middle School Mathematics Curriculum for English-Language Learners

Abstract: Hispanic English-language learners and other students learning English are failing in K-12 mathematics. The field has not responded with mathematics curricula designed for this population, especially at the middle grades. In response to this academic crisis, the Help with English Language Proficiency (HELP) Math program for middle school students was created. HELP Math is a Web-based supplemental curriculum composed of a series of rich interactive lessons that essentialize mathematical vocabulary and academic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 9 publications
1
32
0
Order By: Relevance
“…In each lesson, students were also introduced key vocabularies with scaffolded instruction throughout the lesson to support students' language needs. Learning takes on meaning when teachers connect future learning to prior knowledge and experiences (Garza, 2009;Keck-Staley, 2010;Santamaria, 2009) and support students with scaffolding (Freeman & Crawford, 2008;Gersten et al, 2007). The explicit communication of academic expectations and priming background knowledge of the Latino students may have contributed to the positive academic gains.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In each lesson, students were also introduced key vocabularies with scaffolded instruction throughout the lesson to support students' language needs. Learning takes on meaning when teachers connect future learning to prior knowledge and experiences (Garza, 2009;Keck-Staley, 2010;Santamaria, 2009) and support students with scaffolding (Freeman & Crawford, 2008;Gersten et al, 2007). The explicit communication of academic expectations and priming background knowledge of the Latino students may have contributed to the positive academic gains.…”
Section: Discussionmentioning
confidence: 99%
“…Longitudinal research has shown that Latino students' early literacy proficiency at kindergarten predicted their elementary (Reardon & Galindo, 2007) and middle school mathematics achievement (Lopez, Gallimore, Garnier, & Reese, 2007). As a result, mathematics learning can be especially challenging for many Latino students due to the added linguistic barriers in the existing difficulties of understanding mathematics language (e.g., terms such as coefficient and exponent) (Freeman & Crawford, 2008). Integration of language development activities in mathematics instruction becomes an imperative component for Latino students (Padron, Waxman, & Rivera, 2002).…”
Section: Shumate Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…Adaptations mediate cognitive and linguistic difficulties, as well as cultural or linguistic discontinuities, through the use of a variety of instructional scaffolds to reduce frustration, not only for ELLs with LD but for other groups of struggling learners, as well (August et al, 2005;Echevarria & Graves, 2007;Fang, 2006;Freeman & Crawford, 2008;Hart, 2009;Santamaria, Fletcher, & Bos, 2002;Szpara & Ahmad, 2007).…”
Section: Adaptations To Support Learning For All Studentsmentioning
confidence: 99%
“…Most of the studies related to English language and mathematics focus on teaching mathematics to students who are also learning English, rather than addressing the academic and job related needs of students who are going to be professionals in the area of mathematics teaching (Freeman & Crawford, 2008;Hodgen & Marshall, 2005). In a similar vein, Hendrik and Mji's (2010) study focuses on an 'aid' that would assist learners in relating mathematics terms and concepts in English with terms in their own languages.…”
Section: Introductionmentioning
confidence: 99%